2019
DOI: 10.1002/jssc.201900274
|View full text |Cite
|
Sign up to set email alerts
|

Unique phenolic constituent in Cimicifuga dahurica (Turcz.) Maxim. through Box–Behnken design and response surface methodology

Abstract: Cimicifuga dahurica (Turcz.) Maxim. exerts significant antioxidative due to its high phenolic constituent content. In this study, the extraction condition of the phenolic constituents and antioxidant effect was optimized by the Box-Behnken design and response surface methodology. Eleven main bioactive analytes of Cimicifuga dahurica (Turcz.) Maxim. were simultaneously quantified by high-performance capillary electrophoresis with diode-array detector to assess the effect of extraction technology. The optimal ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The change in solvent polarity might justify this result as the ethanol concentration changes [ 51 ]. A recent study, Yu et al [ 52 ] observed the same effect of ethanol concentration on antioxidant capacity of Cimicifuga dahurica (Turcz.) extracts.…”
Section: Resultsmentioning
confidence: 78%
“…The change in solvent polarity might justify this result as the ethanol concentration changes [ 51 ]. A recent study, Yu et al [ 52 ] observed the same effect of ethanol concentration on antioxidant capacity of Cimicifuga dahurica (Turcz.) extracts.…”
Section: Resultsmentioning
confidence: 78%
“…diseases (Qiu et al, 2006). 9,19-Cycloalkane triterpenoids, amides and phenolic acids have been reported as the main components (Zhang et al, 2002), showing the functions of anti-inflammation (Pang et al, 2020;Thao et al, 2018;Thao, Luyen, Lee, Kim, Dat, et al, 2017), anti-oxidation (Qin et al, 2016;Yu et al, 2019), antitumor (Hao et al, 2020;Huyen et al, 2018), neuroprotection (Kim et al, 2018;Lv et al, 2017) and alleviating menopausal syndrome (Wuttke et al, 2014).…”
mentioning
confidence: 99%